The gold standard in theory and practice - Hawtrey, R. G. (London Longmans, Green, 1947)
The book examines the nature and purpose of a gold standard as a medium of exchange. It also considers the history of gold standard from 1717 to 1937 and its usage in the countries of Europe and United States.
Includes index
Includes bibliographical footnotes
usc 15/9/17
Loans
Keywords: Currency question; Gold standard; Credit